Proliferação, apoptose e morfometria do útero e da placenta de ratas hipertireóideas na gestação e no pós-parto associadas ao desenvolvimento fetal - Edmilson Santos de Freitas (2006)
In two different experiments, the hyperthyroidism effect was evaluated on the proliferation rate, apoptosis and morphometry of uterus and placenta during gestation, fetal development and after birth. In the first experiment, 36 sexually mature female Wistar rats were distributed in two groups of 18 animals: hyperthyroid and euthyroid (control). The female rats were mated and after seven, 14 and 19 days of gestation, six animals/group were sacrificed. The uterus and the placenta were weighed and submitted to histomorphometric and immunohistochemical evaluation to determine the cellular proliferation rate and apoptosis, using the antibodies anti-CDC-47 and anti-caspase-3, respectively. The fetuses were quantified and weighed individually. In the second experiment, 12 sexually mature female Wistar rats were distributed in two groups of six animals: hyperthyroid and euthyroid (control). The female rats were mated and sacrificed after two days pos-parturition. The uteri were evaluated on the same way as the first experiment. The rats ovaries were evaluated in both experiments. The hyperthyroidism has increased the ovulation and conception rates without disturbing the size and viability of the fetuses. In the pregnant uterus, the hyperthyroidism did not change the layers thickness, proliferation rate or apoptosis. However, on the placenta, the hyperthyroidism increased the medium diameter of the trophoblastic cells and also the thickness and proliferation rate of the cytotrophoblast at 14 days of gestation. During the uterine involution, the hyperthyroidism raised the proliferation rate significantly and reduced the apoptosis rate of the uterine layers. In conclusion, the hyperthyroidism increases the conception rate because of the ovulation gain and induces significant placentary changes during pregnancy and increases the proliferation rate and reduces the apoptosis rate of the uterine layers two days pos-parturition.